Podcasting as an Innovative Pedagogical Tool in Social Work Education - Mim Fox; Jonathan B. Singer (Social Sciences)
Podcasting as a means of educational delivery has been slowly increasing since the introduction of podcasting to the consciousness of the general public in 2004. In parallel, social work education has experienced a global increase in online and remote delivery. Social workers globally have embraced social work content podcasts as a means of providing, and supplementing, their traditional pedagogy. In this article, the authors, both international podcasting social work academics, present an innovative framework for podcasting pedagogy and discuss co-production of podcasts as a form of teaching and learning co-design that is grounded in social work approaches to knowledge creation, dissemination, and scholarship.